Conducting co-creation for public health in low and middle-income countries: a systematic review and key informant perspectives on implementation barriers and facilitators - Giuliana Raffaella Longworth; Oritseweyinmi Erikowa-Orighoye; Ebuka Miracle Anieto; Danielle Marie Agnello; Jorge Raul Zapata-Restrepo; Caroline Masquillier; Maria Giné-Garriga (BMC, 2024)
Abstract Background There has been an increase in the use of co-creation for public health because of its claimed potential to increase an intervention's impact, spark change and co-create knowledge. Still, little is reported on its use in low-and-middle-income countries (LMICs). This study offers a comprehensive overview of co-creation used in public-health-related interventions, including the interventions' characteristics, and reported implementation barriers and facilitators. Methods We conducted a systematic review within the Scopus and PubMed databases, a Google Scholar search, and a manual search in two grey literature databases related to participatory research. We further conducted eight interviews with first authors, randomly selected from included studies, to validate and enrich the systematic review findings. Results Through our review, we identified a total of twenty-two studies conducted in twenty-four LMIC countries. Majority of the interventions were designed directly within the LMIC setting. Aside from one, all studies were published between 2019 and 2023. Most studies adopted a co-creation approach, while some reported on the use of co-production, co-design, and co-development, combined either with community-based participatory research, participatory action research or citizen science. Among the most reported implementation barriers, we found the challenge of understanding and accounting for systemic conditions, such as the individual's socioeconomic status and concerns related to funding constraints and length of the process. Several studies described the importance of creating a safe space, relying on local resources, and involving existing stakeholders in the process from the development stage throughout, including future and potential implementors. High relevance was also given to the performance of a contextual and/or needs assessment and careful tailoring of strategies and methods. Conclusion This study provides a systematic overview of previously conducted studies and of reported implementation barriers and facilitators. It identifies implementation barriers such as the setting's systemic conditions, the socioeconomic status and funding constrains along with facilitators such as the involvement of local stakeholders and future implementors throughout, the tailoring of the process to the population of interest and participants and contextual assessment. By incorporating review and interview findings, the study aims to provide practical insights and recommendations for guiding future research and policy.